The Regulatory Functions of lncRNAs on Angiogenesis Following Ischemic Stroke - Gan, Li; Liao, Shengtao; Xing, Yu; Deng, Shixiong (Frontiers in Molecular Neuroscience, 2021)
Ischemic stroke is one of the leading causes of global mortality and disability. It is a multi-factorial disease involving multiple factors, and gene dysregulation is considered as the major molecular mechanisms underlying disease progression. Angiogenesis can promote collateral circulation, which helps the restoration of blood supply in the ischemic area and reduces ischemic necrosis following ischemic injury. Aberrant expression of long non-coding RNAs (lncRNAs) in ischemic stroke is associated with various biological functions of endothelial cells and serves essential roles on the angiogenesis of ischemic stroke. The key roles of lncRNAs on angiogenesis suggest their potential as novel therapeutic targets for future diagnosis and treatment. This review elucidates the detailed regulatory functions of lncRNAs on angiogenesis following ischemic stroke through numerous mechanisms, such as interaction with target microRNAs, downstream signaling pathways and target molecules.